Guinness World Records, 2020. Gamer's edition - Glenday, Craig; Ali-A, 1993-; Guinness World Records Limited (London : Guinness World Records Limited, 2019)
Profiles video gaming systems and games from 2019, offering gaming records, lists of award-winning games, interviews with game designers and industry experts, key developments in gaming hardware, gaming tips and trivia, and more.
Includes index.
Young Adult
Keywords: Video games -- Miscellanea